Investigating the causes of job stress among employees: a case of manufacturing company in Malaysia (Kendek Group of Companies) / Nurul Suhada Sehat - Sehat, Nurul Suhada (Faculty of Business and Management, 2018)
This study is to investigate the causes of job stress among employees in Kendek Group of Companies. Five objectives have been determined in order to achieve the purpose of this study. First is to identify the relationship between work overload and job stress. Second objective is to identify the relationship between role conflict and job stress. Third, to identify the relationship between role ambiguity and job stress. Fourth, to identify the relationship between work-family conflict and job stress and the last one is , to identify the most significant factor that are related to job stress. The population of this study consists of 113 employees from Kendek Group of Companies, while the sample consists of 86 respondents. The data were collected by distribute 113 questionnaires and 110 returned questionnaires were used in the study. The questionnaires designed based on four independent variables that are expected to affect job stress which are work overload, role conflict, role ambiguity and work-family conflict. To analyses the data, descriptive, correlation, and regression analyses was used. Hence, the results from this study reveal that there is a positive relationship between three independent variables which work overload, role conflict and role ambiguity towards job stress. It also show that, there is no significant relationship between work-family conflict and job stress. In addition, there are many others factors that may cause job stress which are not included in this research intend to suggests to include others factors as discuss in chapter 5. The sample of this study only limited to the employee that are working in Kendek Group of Companies.